Catando a poesia derramada no chão: constelações femininas na obra de Chico Buarque - Margarida Maria Alacoque Chaves de Sousa (2015)
This paper presents a constellation reading of the work of Chico Buarque, having as theoretical framework the texts of Walter Benjamin, especially the Theses on the Philosophy of History, in the attempt to stablish the new images of women that were included in his already extensive gallery of female profiles, mostly the ones that have been created since the 1990s. The hypothesis is that Chico Buarque, as the ragpicker of Baudelaire, quoted by Benjamin, gathers, compares, and sews remains of characters of our cultural universe (canonical characters of literature and MPB songs) in order to build a mosaic of his most recent female figurations. This method leads to fragmented, complex, and multifaceted characters, that move away from the stereotypes which commonly stigmatized woman with closed, idealized, and oppressive images